AMPLIFIKASI FRAGMEN 0,4 KB DAERAH D-LOOP DNA MITOKONDRIA LIMA INDIVIDU SUKU BALI TANPA HUBUNGAN KEKERABATAN DENGAN METODE POLYMERASE CHAIN REACTION (PCR) - Ratnayani, K.; Chandra Yowani, Sagun; Syane S, Liangky (Jurnal Kimia (Journal of Chemistry), 2012)
The human mitochondrial DNA (mtDNA) has higher polimorfism level than nucleous genom, and it is maternally transmitted. D-Loop is a non-sense region in human mtDNA that has the highest polimorfism. Generally, the aim of this research is to find out the variation in D-Loop region of mtDNA in some Balinese without family correlation. For that reason, this research was brought out to determine the sequences of nucleotide of D-Loop region in five normal Balinese from different families without correlation. The specific aim of this research is to amplify the 0,4 kb fragment of mtDNA D-Loop region in five Balinese above, using the PCR methode. In conducting the PCR, the temperature of annealing of primer and the weight of template of mtDNA were optimized. Several phases that have been conducted : 1). Lisis of the cavum oris epithelium; 2). Quantation of DNA; 3). Reaction PCR; 4). Result of PCR detection with agarosa gel electroforesis The result of this research is the amplification of 0,4 kb fragment of D-Loop region in mtDNA by PCR. This research also found the optimum temperature annealing, which was 55 0C, and the optimum weight of template of DNA which was ± 0,688 ?g.
Keywords: DNA mitochondrial, D-Loop, amplification, quantitation, optimation